The Love and Belonging Needs Character in The Girl on The Trains Novel - Nina Farlina; Nadia Khaleda (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2019)
This research aims to understand what needs that Rachel Watson as the main character in The Girl on the Train novel is trying to fulfill by riding the train every day and how she fulfills her safety and the love and belonging needs using Abraham Maslow’s hierarchy of human needs. Before studying the needs, the writer analyzes the main character’s character and characterization. This research is using qualitative method and descriptive analysis to analyze the love and belonging needs and esteem needs of the main character. The result of this research is Rachel Watson as the main character has some noticeable characters such as imaginative, alcoholic, and liar. She fulfills her safety needs by killing her ex-husband and fulfills her love and belonging needs by trying to seek attention from her ex-husband, Tom Watson and from Scott Hipwell. Rachel fails to have the love from both Tom and Scott but finally she realizes that she is always loved by her friend, Cathy. Rachel successfully satisfies her needs until the third stage of the hierarchy: love and belonging needs.